(3QSGdI aj UaI GdMceIs - (3NGdO Hf jRjO Hf eYGhjg Hf CHj SajGf, CHh gGTe,J (B90 (3g` s
(3ChdgG (B:s
(3HSe Gddg GHJOF hYdjg Jhcdi hHg fSJYjf Efi QCjJ GdfGS WdHhG UfYI GdMceI ai cd YUQ hQCjJ GdMceGA bO cQghG EPGYJgG hUGfhgG Yf GdLedI s
(3BNQgG (B:s
(3aNP ef GdfaS aajg GdfGQ cGefI hGdghGA cGef aNP efg GdfUa hef GdGQV HGdeGA GdfUa Ke GYbOgG ai GdbQYI hGdYejG HfGQ djfI Ef TGA Gddg JYGdi hMOg hgh MSHfG hfYe GdeYjf hGdMeO ddg QH GdYGdejf hUdhGJg Ydi fHi GdQMeI eMeO hCdg GdWGgQjf Je s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B300 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B98s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs